The transfer of land management rights (Public functions or private functions) in relation to the privatization of PT. Kereta Api Indonesia (Persero) - Dewi, Ayu Trisna; Kamello, Tan; Lubis, M. Yamin; Ikhsan, Edy (Edelweiss Applied Science and Technology, 2024)
In the Dutch East Indies, there were two different kinds of railway companies: staats spoorwegen and verenigde spoorwegen. This is when the history of PT. Kereta Api Indonesia (Persero) started. The operational goals of PT. Kereta Api Indonesia (Persero) changed from being socially focused to profit-oriented in 1998 as a result of the business’s status change from public corporation to state-owned enterprise (BUMN). The BUMN Law, which established the idea of privatization, brought about this shift. As a result, PT. Kereta Api Indonesia (Persero) is also bound by the standards of sound corporate governance and business judgment, which causes a number of problems. These concerns include the form of the transfer of civil rights in the management of state land, the relationship between the privatization of PT. Kereta Api Indonesia (Persero) and the transfer of civil rights in the management of state land, and the renewal of the privatization concept in compliance with the 1945 Constitution and Pancasila. Using legislative, conceptual, historical, and case techniques, the research is prescriptive and combines normative and empirical legal research. Primary and secondary data are among the sources and methods used for data gathering. Fieldwork and literature reviews are used to gather data, which is then qualitatively examined. The agreement that forms the foundation for the transfer of PT. Kereta Api Indonesia’s civil rights as the owner of management powers over the state makes the link between privatization and the transfer of civil rights very clear. The 1945 Constitution and Pancasila’s philosophical and constitutional underpinnings, which place the goal of transferring civil rights in the management rights over state land on the basis of social justice for the greatest welfare of the Indonesian people, serve as the basis for the revision and harmonization of the privatization concept related to the transfer of civil rights in the management rights of PT.KAI.